Effect of utilising of sugarcane bagasse fibers on mechanical properties of composite materials ـــ a review - Hamid, Marawan M.; Taher, Muntadher J.; Abbas, Hassan Ali (Edelweiss Applied Science and Technology, 2024)
Natural fibers are frequently employed in the engineering of building materials. However, the highly beneficial nature of using sugarcane fiber waste imbedded with concrete as a construction material may enhance the ductility and crack control of brittle concrete. This review summarized the effect of using sugarcane bagasse fibers in a several of concrete types and illustrated the significant leverage on the mechanical properties of concrete. Because of its biodegradable features and chemical components, sugarcane bagasse (SCB) has prompted a lot of attention as a promising and flexible component in composite materials. Material researchers have been motivated to develop "green" materials with low pollutant indices by the desire to discover low-cost strategies to lessen environmental effect. The three categories of sugarcane byproducts discovered and categorized were bagasse fiber, bagasse sand, and bagasse ash.